Check list of the birds of the Azores. - Le Grand, Gérald (2011)
This check list contains all records from the Azores up to December 1982 from personal observations and bibliography of the Azores (see Le Grand & Furtado (1982) Bol. Mus. Mun. Funchal 34 (150): 142-190). The relative status of the species mentioned is intended only as a guide, the number of some migratory and wintering species often vary from year to year and lack of observers difficult to obtain accurate status for many species. When races or subspecies are recognized it is indicated. Resident species are, see also table in appendix. Our division would be grateful to receive any records from residents or visiting birdwatchers. Such records should be sent to our office at the University of the Azores. To ensure accuracy in records, it would be appreciated if all records be accompanied by detailed description (photography when possible) for any sighting, in particular for difficult or rare species.